An Enzymatic Transesterification Of Refined, Bleached And Deodorized Palm Oil During Dry-Fractionation In A Pilot-Scale Fractionation Plant - Ker, Yee Ping (2002)
Enzymatic transesterification of refined, bleached and deodorized (RBD) palm oil during dry-fractionation was studied using commercially prepared immobilized lipase from Rhizomucor miehei (Lipozyme 1M 60, Novozyme, Bagvaerds, Denmark). A 5-liter pilot-scale fractionation apparatus was used. The enzyme concentrations used were of 1, 1.5, 2.0, 2.5, 3.5 and 4.5 wt%, and was added into the crystallizer of the fractionation apparatus along with the RBD palm oil. Each transesterification process was carried out in five replicates for 12 hours based on a typical cooling profile for palm oil fractionation in palm oil refineries. The initial temperature of the cooling process was 65°C and the final temperature was 25°C. After the cooling process, the liquid fraction was extracted from the transesterified RBD palm oil through filtration using a piece of commercial filtercloth of 600 um porosity (Netzsch, Selb, Germany).